DETERMINATION OF HAFNIUM IN ZIRCONIUM DIOXIDE USING INDUCTIVELY COUPLED PLASMA MASS SPECTROMETRY (ICP-MS) - HUYNH , VAN TRUNG; NGUYEN , XUAN CHIEN; LE , HONG MINH; DANG , DUC NHAN (Nuclear Science and Technology, 2013)
A method for determination of hafnium (Hf) in zirconium dioxide (ZrO2) using inductively coupled plasma mass spectrometry (ICP-MS) is proposed. The method involves the decomposition of ZrO2 sample, the chemical separation of Hf from zirconium (Zr) matrix by ion-exchange chromatography with sulfuric acid as a medium of sample solution and an eluent as well. The methods are suitable for analysis of Hf impurity in ZrO2 of nuclear grade. The procedure was well applied for determination of Hf in ZrO2 product of the Institute for Technology of Radioactive and Rare Elements (ITRRE), VINATOM.